SEVERITY OF TB CLASSIFIED BY MODIFIED BANDIM TB SCORING ASSOCIATES WITH THE SPECIFIC SEQUENCE OF ESXA GENES IN MDR-TB PATIENTS - Dewi, Desak Nyoman Surya Suameitria; Mertaniasih, Ni Made; Soedarsono, Soedarsono (African Journal of Infectious Diseases (AJID), 2020)
Background: The severity of pulmonary TB and detection of multidrug-resistant (MDR-TB) TB strains as potential causative agents could be crucial for the determination of treatment success. This study aimed to analyze the association between the specific sequences of the full esxA gene from MDR-TB sputum isolates and the severity class of MDR-TB patients. Material and Methods: A total of 98 sputum samples that were suspected to be MDR-TB were collected from Dr. Soetomo, Surabaya, Indonesia, from September until December 2016. A total of 24 isolates from the 98 patients were confirmed to have positive MDR-TB based on the GeneXpert test. MDR-TB isolates were tested using PCR targeting 580 bp encompassing the full esxA gene, and the resulting amplicon was sequenced. The severity class of the pulmonary TB patients was assessed using modified Bandim TB scoring. Results: The patient severity classification resulted in a moderate and severe degree of TB in 38% and a mild degree of TB in 63% of patients. Visualization of the PCR results showed that all MDR-TB samples were positive for the 580 bp band, and the sequence results showed 100% homology with that of the virulent wild-type M. tuberculosis H37Rv (NC_000962.3). Conclusions: In the current study, an association between the characteristics of the full esxA gene and the severity class of MDR-TB patients has yet to be found. However, the homologous sequence of all samples, associated with various degrees of disease severity, possess 100% identity with that of wild-type M. tuberculosis H37Rv.